2022
DOI: 10.1590/0104-1428.20220013
|View full text |Cite
|
Sign up to set email alerts
|

Polymer composite produced with Brazil nut residues and high impact polystyrene

Abstract: Solid residues from agroindustry often accumulate and cause environmental imbalance. An alternative to this is to use this residue as a reinforcement in polymers. The achievement of this work was to characterize a composite with a polystyrene matrix reinforced with Brazil nut shells residues. The residues were cleaned and ground to then produce the samples via injection molding with the proportions of 0%, 2.5% and 5% of load. The specimens were characterized using mechanical tensile testing and thermogravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In the second deposition step (475 to 600 ºC), this is associated with the end of the degradation of acrylonitrile. It was observed that between ~ 200 ºC and 325 ºC other decompositions occur; however, the reactions involved are volatiles that exist in the ABS [36][37][38], similar observations are also described in the literature [39][40][41][42].…”
Section: Thermogravimetric and Calorimetric Analysis (Tga/dsc)supporting
confidence: 80%
“…In the second deposition step (475 to 600 ºC), this is associated with the end of the degradation of acrylonitrile. It was observed that between ~ 200 ºC and 325 ºC other decompositions occur; however, the reactions involved are volatiles that exist in the ABS [36][37][38], similar observations are also described in the literature [39][40][41][42].…”
Section: Thermogravimetric and Calorimetric Analysis (Tga/dsc)supporting
confidence: 80%
“…Thus, in the face of growing environmental concerns and the possibility of depleting oil reserves, natural fibers can be an environmentally friendly alternative, in line with the principles of sustainable development. These materials are known to be renewable and biodegradable, and they have been widely used in various industrial and engineering applications [11][12][13][14][15][16]. According to the annual report of the Discover Natural Fibers Initiative (DNFI), shown in Table 2, in the year 2023, global production of natural fibers was estimated at 31.9 million tons, surpassing the production of the year 2020.…”
Section: Bcmentioning
confidence: 99%
“…Another alternative to address the excessive accumulation of plant residues is the utilization of these residues as fillers in polymeric composites and other Eng 2024, 5 conventional engineering materials. Within this context, waste management brings benefits to both organizations and society, promoting the commercialization of these materials and generating income through recycling and sustainability practices [16]. This is highly advantageous, considering that Brazil is currently one of the main producers of various natural fibers, thanks to the great diversity of these materials in the country, especially those originating from the Amazon [34][35][36].…”
Section: Bcmentioning
confidence: 99%